Pengaruh Faktor Motivasi Dan Persepsi Pengunjung Terhadap Keputusan Pembelian Tiket Pada Konser Act: Sweet Mirage In Jakarta - Ulfi Maranisya; Adelin Vinico Yuanita (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explore the motivational factors and perceptions of visitors influencing ticket purchasing decisions for the music concert titled Act: Sweet Mirage In Jakarta, featuring the South Korean group TOMORROW X TOGETHER. The study involved a sample of 87 respondents and utilized a quantitative analysis research method with data collected through questionnaires. The multiple linear regression analysis results indicated a regression coefficient value of 0.222 for motivational factors, showing a positive and significant impact on purchasing decisions. Additionally, the regression coefficient value for visitor perception factors was 0.630, indicating a positive impact on purchasing decisions. Both variables collectively influence the ticket purchasing decision for the Act: Sweet Mirage In Jakarta concert, as evidenced by the computed F-value of 8.847, which exceeds the critical F-value of 3.11.